Functional Gastrointestinal Disorders in Patients With Epilepsy: Reciprocal Influence and Impact on Seizure Occurrence - Avorio, Federica; Cerulli Irelli, Emanuele; Morano, Alessandra; Fanella, Martina; Orlando, Biagio; Albini, Mariarita; Basili, Luca M.; Ruffolo, Gabriele; Fattouch, Jinane; Manfredi, Mario; Russo, Emilio; Striano, Pasquale; et al. (Frontiers in Neurology, 2021)
Introduction: The complex relationship between the microbiota-gut-brain axis (MGBA) and epilepsy has been increasingly investigated in preclinical studies. Conversely, evidence from clinical studies is still scarce. In recent years, the pivotal role of MGBA dysregulation in the pathophysiology of functional gastrointestinal disorders (FGID) has been recognized. With this background, we aimed to investigate the prevalence of FGID in patients with epilepsy (PWE) and the possible impact of bowel movement abnormalities on seizure recurrence. Methods: A total of 120 PWE and 113 age-, sex-, and BMI-matched healthy subjects (HS) were consecutively enrolled. A questionnaire to evaluate the presence of FGID (according to Rome III diagnostic criteria) was administrated to all participants. In a subgroup of drug-resistant patients, we administered an ad-hoc questionnaire combining Bristol stool charts and seizure diaries to evaluate seizure trends and bowel movement changes. Results: A higher prevalence of FGID in PWE (62.5%) than in HS (39.8%) was found (p<0.001). The most frequently observed disorder was constipation, which was significantly higher in PWE than in HS (43.3% vs. 21.2%, p<0.001), and was not associated with antiseizure medication intake according to multivariable analysis. In drug-resistant patients, most seizures occurred during periods of altered bowel movements, especially constipation. A significant weak negative correlation between the number of days with seizures and the number of days with normal bowel movements was observed (p=0.04). According to multivariable logistic regression analysis, FGID was significantly associated with temporal lobe epilepsy as compared with other lobar localization (p=0.03). Conclusions: Our clinical findings shed new light on the complex relationship between epilepsy and the MGBA, suggesting a bidirectional link between bowel movement abnormalities and seizure occurrence. However, larger studies are required to better address this important topic.